"DIFFERENTIATED APPROACH TO THE TREATMENT OF INFLAMMATORY PERIODONTAL DISEASES IN PEOPLE WITH CHRONIC VIRAL HEPATITIS" (American Journal of Interdisciplinary Research and Development, 2022)
In the same population of patients, the effect of melody on microcirculation indicators and external respiratory function was noted. Thus, melody in the clinic of internal diseases can be considered as a nadnozological drug with a wide range of clinical effects.